2022
DOI: 10.3389/fpsyg.2022.1006034
|View full text |Cite
|
Sign up to set email alerts
|

The association of fear of movement and postural sway in people with low back pain

Abstract: BackgroundFear of movement is thought to interfere with the recovery from low back pain (LBP). To date, the relationship between fear of movement and postural balance has not been adequately elucidated. Recent findings suggest that more specific fears need to be assessed and put in relation to a specific movement task. We propose that the fear to bend the trunk in a certain direction is distinctly related to the amount of postural sway in different directions. Therefore, our aim was to investigate whether fear… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…However, although there is a lack of evidence on the effect of pain-related anxiety and depression on postural balance, it is theoretically possible that anxiety and depression could affect postural balance ( 16 ). Furthermore, CLBP patients with high fear-avoidance beliefs were not only vigilant but also significantly restricted their range of motion during lumbar flexion and extension ( 18 ). Fear may also disrupt the automaticity of neural control pathways, leading to deficits in trunk motor control and increased trunk variability during maintaining balance, which may also increase the risk of LBP ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, although there is a lack of evidence on the effect of pain-related anxiety and depression on postural balance, it is theoretically possible that anxiety and depression could affect postural balance ( 16 ). Furthermore, CLBP patients with high fear-avoidance beliefs were not only vigilant but also significantly restricted their range of motion during lumbar flexion and extension ( 18 ). Fear may also disrupt the automaticity of neural control pathways, leading to deficits in trunk motor control and increased trunk variability during maintaining balance, which may also increase the risk of LBP ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CLBP patients might modify their motor control strategies in an attempt to prevent further pain ( 16 , 17 ). Postural balance may be influenced by other factors, such as age, impaired proprioception, muscle strength, and coordination ( 16 , 18 ). As there is a lack of evidence on the effect of negative emotions on postural balance in those with CLBP ( 16 ), their relationships remain to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Across the 16 included studies, the average age of the participants was 34.4 (±7.7) years [8,15,23,[50][51][52][53][54][55][56][57][58][59][60][61][62], the average body mass index was 25.5 (±3.0) kg/m² [15, 23, 53-57, 60, 61], and 60.3% (±12.6%) of the participants were female [8,15,23,50,51,[53][54][55][56][57][58][59][60][61]. The average intensity of LBP was 3.4 (±1.5) measured by the numeric rating scale (NRS) and visual analogue scale (VAS) (converted to a score on 10) [8,15,23,[50][51][52][53][54][55][56][57][58][59][60][61][62]. The average disability score was 18.4% (±4.5%) for the Oswestry Disability ...…”
Section: *** Insert Table 2*** *** Insert Figure 2***mentioning
confidence: 99%
“…Individuals with chronic, recurrent, and subacute LBP were included in respectively six [23, 50-52, 60, 62], three [54,56,61], and one [58] study. Six studies did not specify the patient population based on the duration of the LBP complaints [8,15,53,55,57,59]. [8,23,[50][51][52][53][57][58][59][60][61][62], and two studies [8,58].…”
Section: *** Insert Table 2*** *** Insert Figure 2***mentioning
confidence: 99%
“…A review has concluded that poor proprioception was one of the main causes of decreased postural control in elderly patients with low back pain (Sakai et al, 2022). Recent studies also found that fear of movement (Meinke et al, 2022) and functional disability (Sun et al, 2023) were significantly correlated with postural sway in patients with CLBP. Thus, the negative relationship between postural sway and lumbar proprioception in healthy subjects may be explained as an exploratory role of postural sway for acquiring effective proprioceptive information to maintain standing balance, while the ability of postural sway as an exploratory role may be impaired in the CLBP group.…”
Section: Relationships Between Postural Control and Lumbar Propriocep...mentioning
confidence: 99%